2014
DOI: 10.1093/aob/mcu126
|View full text |Cite
|
Sign up to set email alerts
|

The MYB46/MYB83-mediated transcriptional regulatory programme is a gatekeeper of secondary wall biosynthesis

Abstract: MYB46 is a unique transcription factor in that it directly regulates the biosynthesis genes for all of the three major components of the secondary wall as well as the transcription factors in the biosynthesis pathway. As such, MYB46 may offer a useful means for pathway-specific manipulation of secondary wall biosynthesis. However, realization of this potential requires additional information on the 'MYB46-mediated transcriptional regulatory programme', such as downstream direct targets, upstream regulators and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
122
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(124 citation statements)
references
References 90 publications
1
122
0
1
Order By: Relevance
“…Both ZmMYB42 and ZmMYB31 (which did not colocalized with any IVNDFD QTL in the current set of progenies), were shown to have a repressive effect on several genes of the maize lignin pathway [120][121][122]. The ZmMYB146 gene (G31 group), which closely colocalized in bin 10.03 with the IVNDFD QTL having the highest Lod value (Lod = 13.7), is the only maize ortholog of the two Arabidopsis AtMYB46 and AtMYB83 paralogs, which were shown to be the master genes regulating as activator numerous genes involved in the secondary wall biosynthesis [123][124][125][126] . Orthologs of AtMYB46 and AtMYB83 have also been shown with similar roles in woody plants such as EgMYB2 in Eucalyptus, PtMYB4 in pine, or PtrMYB2/3/20/21 in poplar [127][128][129].…”
Section: Monolignol Myb and Nac Genes As Possible Primary Determinamentioning
confidence: 99%
“…Both ZmMYB42 and ZmMYB31 (which did not colocalized with any IVNDFD QTL in the current set of progenies), were shown to have a repressive effect on several genes of the maize lignin pathway [120][121][122]. The ZmMYB146 gene (G31 group), which closely colocalized in bin 10.03 with the IVNDFD QTL having the highest Lod value (Lod = 13.7), is the only maize ortholog of the two Arabidopsis AtMYB46 and AtMYB83 paralogs, which were shown to be the master genes regulating as activator numerous genes involved in the secondary wall biosynthesis [123][124][125][126] . Orthologs of AtMYB46 and AtMYB83 have also been shown with similar roles in woody plants such as EgMYB2 in Eucalyptus, PtMYB4 in pine, or PtrMYB2/3/20/21 in poplar [127][128][129].…”
Section: Monolignol Myb and Nac Genes As Possible Primary Determinamentioning
confidence: 99%
“…], Rengel et al, 2009) and studies in the in vitro system (Demura et al, 2002;Ohashi-Ito et al, 2010;Zhong et al, 2010;Yamaguchi et al, 2011) have identified many genes involved in xylem cell differentiation. These include VND family genes and SCW-related genes encoding MYB transcription factors (McCarthy et al, 2010;Ko et al, 2012Ko et al, , 2014Zhong and Ye, 2012;Hussey et al, 2013); based on this information, NAC-MYB-based transcriptional networks have been proposed for xylem vessel cell differentiation . Moreover, proteome data have been reported for xylem tissues of hybrid aspen (Populus spp.…”
mentioning
confidence: 99%
“…MYB83 is a close homolog of and acts redundantly with MYB46. MYB46/MYB83 transcription factors are master regulators of secondary cell wall formation in Arabidopsis, directly regulating expression of genes involved in lignin, cellulose and hemicellulose biosynthesis, including among others, SND1, CESA4 , CESA7, CESA8 , MYB58, MYB56, and MYB63 (Mccarthy et al, 2009; Ko et al, 2014). Thus, MYB83 appears to be a key component of cell wall modifications in downstream (late) plant defense responses.…”
Section: Discussionmentioning
confidence: 99%